2013
DOI: 10.4172/1948-5956.s18-002
|View full text |Cite
|
Sign up to set email alerts
|

Metabonomics: on the Road to Detect Diagnostic Biomarkers in Endemic (Balkan) Nephropathy. Evaluation in a Retrospective Pilot Project

Abstract: Introduction: Endemic (Balkan) Nephropathy is a chronic renal disease mainly affecting rural populations in the valleys of the Danube. In the absence of renal replacement therapy, it leads to fatal kidney failure and is significantly associated with upper urothelial carcinoma. Bread poisoning with aristolochic acids is now widely accepted. The source of this toxic substance is considered to be Aristolochia clematitis, a perennial plant that invades farming fields. The poisoning with aristolochic acids was sugg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…This study also suggested that metabonomic assessment could be predictive of impending morbidity before conventional criteria can diagnose BEN. Similar metabonomic approach was also applied to surplus of urine samples collected from Belgian women (acutely and mistakenly exposed to AA through diet pills) and Croatian patients (chronically exposed to AA through contaminated food) [65] (Figure 2). Interestingly, a clear discrimination of the Belgian patients from healthy volunteers was shown, and urine samples collected from individuals living in Croatian endemic regions as compared to Croatian inhabitants from non-endemic villages tended to separate from each other.…”
Section: Nephrotoxicity Assessment By the 'Omics' Approachmentioning
confidence: 99%
“…This study also suggested that metabonomic assessment could be predictive of impending morbidity before conventional criteria can diagnose BEN. Similar metabonomic approach was also applied to surplus of urine samples collected from Belgian women (acutely and mistakenly exposed to AA through diet pills) and Croatian patients (chronically exposed to AA through contaminated food) [65] (Figure 2). Interestingly, a clear discrimination of the Belgian patients from healthy volunteers was shown, and urine samples collected from individuals living in Croatian endemic regions as compared to Croatian inhabitants from non-endemic villages tended to separate from each other.…”
Section: Nephrotoxicity Assessment By the 'Omics' Approachmentioning
confidence: 99%